Polyamide materials and separation membranes containing lithium ion sieves and methods of making the same

CN119320492BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310878059.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2026-10-13
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

[0004]本发明的目的是为了克服现有技术存在的上述镁锂分离效率不高的问题,提供一种含锂离子筛的聚酰胺材料和分离膜及它们的制备方法,该分离膜能够以较高的分离系数实现镁锂分离

Benefits of technology

[0013]本发明提供的聚酰胺材料,当应用于镁锂分离时,能够获得较高的分离系数和水通量,并且锂离子筛能够稳定的负载在聚酰胺材料上。采用含有本发明提供的含所述聚酰胺材料的分离膜,能够以较高的分离系数实现镁锂分离,具有较高的锂透过率和较高的水通量。并且,锂离子筛被氨基硅烷改性后,通过键合的方式负载在所述分离膜上,如此结构更稳定,多次使用也不会使得锂离子筛脱落,性能更稳定,更适合实际使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present application relates to the field of separation and extraction, and discloses a lithium ion sieve-containing polyamide material, a separation membrane and a preparation method thereof.The preparation method of the lithium ion sieve-containing polyamide material comprises the following steps: using a dispersion liquid containing a polyamine and a solution containing a polyacyl chloride, and forming the polyamide material through interfacial polymerization; wherein the dispersion liquid containing the polyamine further contains an amino-silane modified lithium ion sieve. When the membrane containing the polyamide material is applied to magnesium-lithium separation, a higher magnesium-lithium separation coefficient can be obtained, and the performance of the membrane is more stable, which is more suitable for actual use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of separation and extraction, and more specifically, to a polyamide material containing a lithium ion sieve, a separation membrane, and a method for preparing them. Background Technology

[0002] The vast majority of my country's lithium resources are found in the brines of salt lakes. Besides lithium ions, these lakes also contain large amounts of magnesium and sodium ions. According to the diagonal rule, magnesium and lithium ions have similar radii and properties, making their separation difficult. A high magnesium-to-lithium ratio is a major characteristic of my country's salt lakes, thus purifying lithium from them presents a significant challenge.

[0003] Currently commercially available membranes exhibit very low separation efficiency for magnesium and lithium ions. Improvements in magnesium-lithium separation efficiency are attributed to high rejection rates for divalent magnesium ions and high permeability to monovalent lithium ions. Existing technologies typically enhance magnesium-lithium separation efficiency by increasing the magnesium ion rejection rate. Therefore, there is an urgent need to develop a technology that can simultaneously improve the rejection rate of divalent magnesium ions and the permeability to monovalent lithium ions, thereby achieving higher separation efficiency for magnesium and lithium. Summary of the Invention

[0004] The purpose of this invention is to overcome the problem of low magnesium-lithium separation efficiency in the prior art, and to provide a polyamide material containing a lithium ion sieve, a separation membrane, and a method for preparing them, wherein the separation membrane can achieve magnesium-lithium separation with a high separation coefficient.

[0005] To achieve the above objectives, a first aspect of the present invention provides a polyamide material containing a lithium-ion sieve, the material comprising a polyamide skeleton and structural units as shown in formula (I) connected to the polyamide skeleton.

[0006]

[0007] In formula (I), R1 is selected from H, C1-C6 alkyl groups and C1-C6 amino groups; R2 is selected from H, -O-M3 groups and C1-C6 alkyl groups; and M1, M2 and M3 are each independently lithium ion sieves.

[0008] A second aspect of the present invention provides a separation membrane comprising a separation layer, wherein the separation layer comprises a polyamide material containing a lithium ion sieve as described in the first aspect.

[0009] A third aspect of the present invention provides a method for preparing a polyamide material containing a lithium ion sieve, the method comprising: using a dispersion containing a polyamine and a solution containing a polyacrylamide chloride, and performing interfacial polymerization to form the polyamide material;

[0010] The dispersion containing polyamines also contains an aminosilane-modified lithium-ion sieve.

[0011] The fourth aspect of the present invention provides a method for preparing a separation membrane, the method comprising the method for preparing a polyamide material containing a lithium ion sieve as described in the third aspect.

[0012] The fifth aspect of the present invention provides a separation membrane prepared by the method described in the fourth aspect.

[0013] The polyamide material provided by this invention, when applied to magnesium-lithium separation, achieves a high separation coefficient and water flux, and the lithium-ion sieve can be stably loaded onto the polyamide material. Using a separation membrane containing the polyamide material provided by this invention, magnesium-lithium separation can be achieved with a high separation coefficient, exhibiting high lithium permeability and high water flux. Furthermore, after the lithium-ion sieve is modified with aminosilane, it is loaded onto the separation membrane via bonding, resulting in a more stable structure that will not detach even after repeated use, leading to more stable performance and greater suitability for practical applications. Detailed Implementation

[0014] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0015] In a first aspect, the present invention provides a polyamide material containing a lithium-ion sieve, the material comprising a polyamide skeleton and structural units as shown in formula (I) connected to the polyamide skeleton.

[0016]

[0017] In formula (I), R1 is selected from H, C1-C6 alkyl groups and C1-C6 amino groups; R2 is selected from H, -O-M3 groups and C1-C6 alkyl groups; and M1, M2 and M3 are each independently lithium ion sieves.

[0018] M1, M2, and M3 can be the same or different. In a preferred embodiment, M1, M2, and M3 are the same.

[0019] The inventors of this invention discovered in their research that when the aforementioned polyamide material is applied to magnesium-lithium separation, a high magnesium-lithium separation coefficient and a high water flux can be obtained. In particular, the lithium-ion sieve is bonded to the polyamide material through a bonding process, which makes the loading of the lithium-ion sieve on the polyamide material more stable. The membrane containing the aforementioned polyamide material will not cause the lithium-ion sieve to fall off even after repeated use, exhibiting stable performance and making it more suitable for practical applications.

[0020] According to the present invention, preferably, the mass content of lithium-ion sieve relative to the total mass of the polyamide material is 0.05-2.2 wt%, more preferably 0.7-1.5 wt% (for example, it can be 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, and values ​​within any two of the above values). The lithium-ion sieve content in the polyamide material can be characterized by X-ray photoelectron spectroscopy.

[0021] According to the present invention, preferably, the lithium ion screen is selected from at least one of aluminum-based hydrotalcite-type bimetallic oxide lithium ion screen, manganese oxide-type lithium ion screen, and titanium oxide-type lithium ion screen, more preferably Li 1.33 Mn 1.67 O4, Li2TiO3 and Li4Mn5O 12 At least one of them.

[0022] Preferably, R1 is propyl and R2 is -O-M3 group.

[0023] Preferably, R1 is propyl and R2 is methyl.

[0024] Preferably, R1 is ethyl-n-propylamino and R2 is methyl.

[0025] Preferably, R1 is ethyl-n-propylamino and R2 is -O-M3 group.

[0026] Under the above conditions, it can be further ensured that polyamide materials have a high separation coefficient and water flux when applied to magnesium-lithium separation.

[0027] A second aspect of the present invention provides a separation membrane comprising a separation layer, wherein the separation layer comprises the polyamide material containing lithium ion sieves as described in the first aspect.

[0028] As described above, when the separation membrane comprises the polyamide material described in the first aspect, it exhibits a high separation coefficient and water flux when applied to magnesium-lithium separation, and the membrane also demonstrates good long-term stability.

[0029] According to a particularly preferred embodiment of the present invention, the material of the separation layer is the polyamide material described in the first aspect.

[0030] According to the present invention, preferably, the separation membrane comprises a bottom layer, a porous support layer and a separation layer in sequence.

[0031] According to the present invention, preferably, the porosity of the bottom layer is 35-60% (for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, or any two of the above values ​​within a range).

[0032] Preferably, the thickness of the bottom layer is 30-150μm, more preferably 50-120μm (for example, it can be 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, or any two of the above values ​​within a range).

[0033] Preferably, the thickness of the porous support layer is 10-100 μm, and more preferably 30-60 μm (for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, or any two of the above values ​​within a range).

[0034] Preferably, the average pore size of the porous support layer is 15-30nm (for example, it can be 15nm, 18nm, 20nm, 23nm, 25nm, 28nm, 30nm, or any two of the above values ​​within a range).

[0035] According to the present invention, preferably, the material of the bottom layer is selected from polyester and / or polyethylene. The bottom layer may be a nonwoven fabric containing the above-mentioned materials.

[0036] According to the present invention, preferably, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryl etherketone, and the weight-average molecular weight of the material of the porous support layer is 50-150 kDa (for example, it can be 50 kDa, 70 kDa, 90 kDa, 100 kDa, 130 kDa, 150 kDa, and any two of the above values ​​within the range and values ​​within the range).

[0037] According to the present invention, preferably, the thickness of the separation layer is 80-110 nm (for example, it can be 80 nm, 90 nm, 100 nm, 110 nm, or any two of the above values ​​within a range).

[0038] According to the present invention, preferably, the average pore size of the separation layer is 0.2-0.3 nm.

[0039] Thirdly, the present invention provides a method for preparing a polyamide material containing a lithium ion sieve, the method comprising: using a dispersion containing a polyamine and a solution containing a polyacrylamide chloride, and performing interfacial polymerization to form the polyamide material;

[0040] The dispersion containing polyamines also contains an aminosilane-modified lithium-ion sieve.

[0041] The inventors of this invention discovered in their research that during the aforementioned interfacial polymerization process, polyamines can form a polyamide framework with polyacrylamide chlorides. Simultaneously, in the presence of amino and carbonyl groups, the aminosilane-modified lithium-ion sieve can also undergo an amidation reaction with other carbonyl groups in the polyacrylamide chloride that have not reacted with the polyamine, forming amide bonds. This results in a structural unit having the structure shown in formula (I) above. Specifically, some carbonyl groups from the polyacrylamide chloride are used to form repeating units of the polyamide with the polyacrylamide chloride, while some carbonyl groups are bonded to the amino-modified lithium-ion sieve. Thus, by bonding the lithium-ion sieve to the polyamide framework via aminosilane, the prepared polyamide material not only exhibits a high separation coefficient and high water flux when applied to magnesium-lithium separation, but also ensures that the lithium-ion sieve is stably loaded onto the polyamide framework, resulting in long-term material stability.

[0042] According to the present invention, preferably, the interface polymerization is performed on a substrate.

[0043] According to the present invention, preferably, the interfacial polymerization method includes: sequentially contacting the surface of a substrate with a dispersion containing a polyamine and a solution containing a polyacrylamide chloride.

[0044] According to the present invention, preferably, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, polyethylenepolyamine, piperazine, m-phenylenediamine and p-phenylenediamine, more preferably polyethyleneimine and / or piperazine.

[0045] When the polyamine is a polymer, the weight-average molecular weight of the polymer can be 10,000-120,000 g / mol (for example, it can be 10,000 g / mol, 20,000 g / mol, 30,000 g / mol, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, 120,000 g / mol, or any two of the above values).

[0046] According to the present invention, preferably, the polyacrylamide chloride is selected from at least one of pyromellitic chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride, more preferably pyromellitic chloride and / or terephthaloyl chloride.

[0047] According to the present invention, preferably, the mass concentration of the polyamine in the dispersion containing the polyamine is 0.1-3 wt%, more preferably 0.5-2.5 wt% (for example, it can be 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, and any two of the above values ​​forming a range or range value).

[0048] According to the present invention, preferably, the aminosilane-modified lithium-ion sieve has a structure as shown in formula (II).

[0049]

[0050] In formula (I), R1 is selected from H, C1-C6 alkyl groups and C1-C6 amino groups; R2 is selected from H, -O-M3 groups and C1-C6 alkyl groups; and M1, M2 and M3 are each independently lithium ion sieves.

[0051] According to a preferred embodiment of the present invention, the method for preparing the aminosilane-modified lithium-ion sieve comprises: mixing the lithium-ion sieve and aminosilane in solution and carrying out a modification reaction under acidic conditions. Using this method, a structure as shown in formula (II) can be prepared. The lithium-ion sieve powder can be first dispersed in water and further dispersed by ultrasonication. Then, aminosilane is added to the dispersion.

[0052] According to the present invention, preferably, the mass ratio of lithium ion sieve to aminosilane is 1:(0.1-1.5).

[0053] Preferably, the mass concentration of lithium ion sieve in the solution is 0.5-1.5 mg / ml (for example, it can be 0.5 mg / ml, 0.6 mg / ml, 0.7 mg / ml, 0.8 mg / ml, 0.9 mg / ml, 1 mg / ml, 1.1 mg / ml, 1.2 mg / ml, 1.3 mg / ml, 1.4 mg / ml, 1.5 mg / ml, and any two of the above values ​​within a range).

[0054] Preferably, the acidic condition is a pH of 1-3.

[0055] Preferably, the conditions for the modification reaction further include: a temperature of 70-90℃ (for example, it can be 70℃, 75℃, 80℃, 85℃, 90℃, or any two of the above values ​​within a range), and a time of 5-8h (for example, it can be 5h, 6h, 7h, 8h, or any two of the above values ​​within a range).

[0056] Under the above conditions, it is possible to further ensure that the structure shown in equation (II) is obtained.

[0057] Preferably, the preparation method of the aminosilane-modified lithium-ion sieve further includes: sequentially centrifuging, first drying, ball milling, and second drying of the material obtained from the modification reaction. The first drying temperature can be 70-120℃, and the time can be 3-6 hours; the second drying temperature can be 80-120℃, and the time can be 3-6 hours. Under the above-mentioned first and second drying conditions, the moisture content in the material can generally be less than 0.05 wt%. Ball milling is used to disperse the material, and it can generally be completed in 25-40 minutes.

[0058] According to the present invention, preferably, in the modified reaction, the lithium ion screen is selected from at least one of aluminum-based hydrotalcite-type bimetallic oxide lithium ion screens, manganese oxide-type lithium ion screens, and titanium oxide-type lithium ion screens, more preferably Li 1.33 Mn 1.67 O4, Li2TiO3 and Li4Mn5O 12 At least one of them.

[0059] According to the present invention, preferably, in the modification reaction, the average particle size of the lithium ion sieve is 10-200 nm (for example, it can be 10 nm, 20 nm, 30 nm, 50 nm, 100 nm, 150 nm, 200 nm, or any two of the above values ​​within a range).

[0060] According to the present invention, preferably, in the modification reaction, the aminosilane is selected from any one of the structures shown in formula (a)-(f);

[0061]

[0062] By using the aforementioned aminosilane, it is possible to ensure that the prepared polyamide material, when applied to magnesium-lithium separation, has higher lithium permeability and higher water flux, as well as better long-term stability.

[0063] According to the present invention, preferably, in the dispersion containing polyamine, the mass concentration ratio of aminosilane-modified lithium-ion sieve to polyamine is 1:(4-60) (for example, it can be 1:4, 1:6, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60 and any two of the above ratios within the range of ratios and values ​​within the range), more preferably 1:(10-50).

[0064] According to the present invention, preferably, relative to 1m 2 The substrate, the amount of aminosilane-modified lithium-ion sieve used is 5-500 mg (e.g., it can be 5 mg, 10 mg, 50 mg, 100 mg, 150 mg, 200 mg, 300 mg, 400 mg, 500 mg, and any two of the above values ​​within a range). It is understood that the amount used is generally greater than the amount that can react and thus exist on the separation layer.

[0065] According to the present invention, preferably, the concentration of the polyacryl chloride in the solution containing polyacryl chloride is 0.01-1 wt%, preferably 0.05-0.5 wt% (for example, it can be 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, and any two of the above values ​​within a range or range thereof).

[0066] The solvent in the solution containing polyacrylamide chlorides is not particularly restricted. For example, it can be Isopar E solution or Isopar G solution (these are isoparaffin solvent oils).

[0067] According to the present invention, preferably, the mass ratio of the polyamine in the dispersion containing the polyamine to the mass of the polyacrylamide in the solution containing the polyacrylamide is (0.1-20):1, more preferably (0.5-10):1.

[0068] According to the present invention, preferably, the contact time between the substrate and the dispersion containing polyamine is 5-100 s, more preferably 10-60 s, and the contact temperature is 20-40°C, more preferably 28-32°C. After contact with the dispersion containing polyamine, the material can be removed, and excess solution on the surface of the material can be removed with a rubber roller.

[0069] According to the present invention, preferably, the contact time between the substrate and the solution containing polyacrylamide chloride is 10-200s, more preferably 20-120s, and the contact temperature is 20-40℃, more preferably 28-32℃.

[0070] According to the present invention, preferably, after contacting the dispersion containing polyamine and the solution containing polyacrylamide chloride, the method further includes: heat treatment of the product after interfacial polymerization.

[0071] Preferably, the heat treatment conditions include: a temperature of 40-150℃, preferably 50-120℃; and a heat treatment time of 0.5-10 minutes, preferably 1-5 minutes. The heat treatment can be performed in a vacuum oven.

[0072] Fourthly, the present invention provides a method for preparing a separation membrane, the method comprising the method for preparing a polyamide material containing a lithium ion sieve as described in the third aspect.

[0073] According to the present invention, preferably, the interface polymerization is performed on a substrate comprising a porous support layer and a bottom layer.

[0074] According to the present invention, preferably, the conditions for the interfacial polymerization further include making the thickness of the separation layer 80-110 nm.

[0075] According to the present invention, preferably, the method further includes the step of preparing a porous support layer on the substrate, the step comprising: coating a solution containing a porous support layer material (e.g., coating can be performed using a doctor blade) on the substrate, and immersing it in water at 10-30°C for 10-60 min to form a porous support layer on the surface of the substrate; the conditions for preparing the porous support layer preferably include such that the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm.

[0076] Preferably, in the solution containing the porous support layer material, the mass concentration of the porous support layer material is 10-20 wt% (for example, it can be 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, and any two of the above values ​​within the range).

[0077] The solvent in the solution containing the porous support layer material is not particularly limited. However, it is preferred that the solvent in the solution containing the porous support layer material is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0078] According to the present invention, preferably, the thickness of the bottom layer is 30-150 μm, more preferably 50-120 μm (for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, or any two of the above values ​​within a range or range of values).

[0079] According to the present invention, preferably, the material of the bottom layer is selected from polyester and / or polyethylene.

[0080] According to the present invention, preferably, the porosity of the bottom layer is 35-60% (for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, or any two of the above values ​​within a range).

[0081] According to the present invention, preferably, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone, and the weight-average molecular weight of the material of the porous support layer is 50-150 kDa.

[0082] The porous support layer material can be dissolved in a solvent, and then the solution can be degassed at 22-28℃ for 1.5-3 hours.

[0083] Fifthly, the present invention provides a separation membrane prepared by the method described in the fourth aspect.

[0084] The present invention will be described in detail below through embodiments. In the following embodiments, the thicknesses of the porous support layer and the separation layer are determined by scanning electron microscopy. The thickness of the separation layer refers to the thickness of the film formed by interfacial polymerization, excluding the influence of the lithium-ion sieve particle size.

[0085] In the following examples, before interfacial polymerization, the average pore size of the porous support layer was measured using a pore size analyzer (model PSDA-20, purchased from Nanjing Gaoqian) for materials containing porous supports and a bottom layer.

[0086] The average pore size of the separation layer was determined using the PEG solute transfer method (see Journal of Membrane Science, 281 (2006), 307-315).

[0087] The content of modified lithium-ion sieves in the membrane (i.e., the content of modified lithium-ion sieves in the separation layer as shown in Table 1) was determined by measuring the metal ion content using X-ray photoelectron spectroscopy (XPS).

[0088] In the following embodiments and comparative examples:

[0089] Examples 1-7 use materials containing porous supports and a bottom layer. The porous support layer on the bottom layer is prepared by a phase inversion method. The specific steps are as follows: A certain amount of polysulfone (weight average molecular weight of 80 kDa) is dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%. The solution is degassed at 25°C for 120 min. Then, the polysulfone solution is coated onto a polyester nonwoven fabric (with a thickness of 75 μm and a porosity of 40%) using a doctor blade. The fabric is then immersed in water at 25°C for 60 min to allow the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase inversion. Finally, the material with porous supports and a bottom layer is obtained after three water washes.

[0090] Example 8 uses a material containing a porous support and a bottom layer. The porous support layer on the bottom layer is prepared by a phase inversion method. The specific steps are as follows: a certain amount of polysulfone (weight average molecular weight of 100 kDa) is dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 20 wt%. The solution is degassed at 25°C for 120 min. Then, the polysulfone solution is coated onto a polyester nonwoven fabric (porosity of 30%) with a thickness of 100 μm using a doctor blade. The fabric is then immersed in water at 22°C for 50 min to allow the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase inversion. Finally, the material containing a porous support and a bottom layer is obtained after three water washes.

[0091] Example 9 uses a material containing a porous support and a bottom layer. The porous support layer on the bottom layer is prepared by a phase inversion method. The specific steps are as follows: a certain amount of polysulfone (weight average molecular weight of 120 kDa) is dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 19 wt%. The solution is degassed at 25°C for 120 min. Then, the polysulfone solution is coated onto a polyester nonwoven fabric (with a thickness of 80 μm and a porosity of 60%) using a doctor blade. The fabric is then immersed in water at 27°C for 45 min to allow the polysulfone layer on the surface of the polyester nonwoven fabric to undergo a phase inversion. Finally, the material containing a porous support and a bottom layer is obtained after three water washes.

[0092] In the following embodiments and comparative examples:

[0093] (1) The water flux of the membrane was obtained by testing as follows: The composite nanofiltration membrane was placed in a membrane tank, and the water permeation rate of the nanofiltration membrane was measured over a certain period of time at 0.6 MPa and a temperature of 25°C. The water flux was then calculated using the following formula:

[0094] J = Q / (A·t), where J is the water flux, Q is the water permeation rate (L), and A is the effective membrane area of ​​the composite nanofiltration membrane (m²). 2 ), where t is time (h);

[0095] (2) The desalination rate and magnesium-lithium separation coefficient of the composite nanofiltration membrane were obtained by the following method: The composite nanofiltration membrane was loaded into the membrane tank. The original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride. After pre-pressurization at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.6 MPa. The concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated by the following formula:

[0096] R = (Cp - Cf) / Cp × 100%, where R is the desalination rate, Cp is the concentration of magnesium chloride or lithium chloride in the original solution (measured by ion chromatography), and Cf is the concentration of magnesium chloride or lithium chloride in the permeate (measured by ion chromatography).

[0097] The lithium-magnesium separation coefficient is calculated using the following formula:

[0098]

[0099] Where S is the lithium-magnesium separation coefficient, and C Li,p and C Li,f The concentrations of lithium ions in the permeate and feed solution, respectively (measured by ion chromatography); C Mg,p and C Mg,f The concentrations of magnesium ions in the permeate and feed solution are respectively (measured by ion chromatography).

[0100] Preparation Example 1

[0101] Lithium-ion sieve powder Li 1.33 Mn 1.67 O4 (20 nm) was dispersed in water and ultrasonically dispersed for 10 min. Then, aminosilane of formula (a) was added to the dispersion to achieve a concentration of 0.5 mg / ml, a lithium ion sieve powder concentration of 0.8 mg / ml, and a lithium ion sieve powder:formula (a) ratio of 1:0.625 (mass ratio). The pH of the reaction system was adjusted to 3 with dilute hydrochloric acid. The reaction was carried out at 80°C for 6 h, centrifuged, and dried (at 80°C for 3 h). The resulting product was then ball-milled for 30 min and dried (at 110°C for 3 h) until the water content was less than 0.05 wt%, yielding aminosilane-modified lithium ion sieve A.

[0102]

[0103] Preparation Example 2

[0104] Lithium-ion sieve powder Li 1.33 Mn 1.67 O4 (20 nm) was dispersed in water and ultrasonically dispersed for 10 min. Then, aminosilane of formula (b) was added to the dispersion to achieve a concentration of 0.8 mg / ml, a lithium ion sieve powder concentration of 0.8 mg / ml, and a lithium ion sieve powder to formula (b) ratio of 1:1 (mass ratio). The pH of the reaction system was adjusted to 3 with dilute hydrochloric acid. The reaction was carried out at 70°C for 6 h, centrifuged, and dried (at 80°C for 3 h). The resulting product was then ball-milled for 30 min and dried (at 110°C for 3 h) until the water content was less than 0.05 wt%, yielding aminosilane-modified lithium ion sieve B.

[0105]

[0106] Preparation Example 3

[0107] Similar to Preparation Example 1, except that the aminosilane shown in Formula (a) is replaced with the aminosilane shown in Formula (e), to obtain an aminosilane-modified lithium-ion sieve C.

[0108]

[0109] Preparation Example 4

[0110] Lithium-ion sieve powder Li₂TiO₃ (100 nm) was dispersed in water and ultrasonically dispersed for 10 min. Then, aminosilane as shown in formula (a) was added to the dispersion to achieve a concentration of 1.2 mg / ml and a lithium-ion sieve powder concentration of 0.8 mg / ml, resulting in a lithium-ion sieve powder to formula (a) ratio of 1:1.5 (mass ratio). The pH of the reaction system was adjusted to 2 using dilute hydrochloric acid. The reaction was carried out at 90°C for 6 h, centrifuged, and dried (at 80°C for 3 h). The resulting product was then ball-milled for 30 min and dried (at 110°C for 3 h) until the water content was less than 0.05 wt%, yielding aminosilane-modified lithium-ion sieve D.

[0111] Preparation Example 5

[0112] Lithium-ion sieve powder Li 1.33 Mn 1.67 O4 (200 nm) was dispersed in water and ultrasonically dispersed for 10 min. Then, aminosilane of formula (a) was added to the dispersion to achieve a concentration of 2.2 mg / ml. The lithium ion sieve powder concentration was 1.3 mg / ml, resulting in a lithium ion sieve powder to formula (a) ratio of 1:1.7 (mass ratio). The pH of the reaction system was adjusted to 1 using dilute hydrochloric acid. The reaction was carried out at 70°C for 5 h, centrifuged, and dried (at 80°C for 3 h). The resulting product was then ball-milled for 30 min and dried (at 110°C for 3 h) until the water content was less than 0.05 wt%, yielding aminosilane-modified lithium ion sieve E.

[0113] Example 1

[0114] Use a material containing a porous support layer and a bottom layer (area 400cm²) 2 The material was contacted with a dispersion of polyethyleneimine (weight-average molecular weight 100,000 g / mol) at a concentration of 0.8 wt% for approximately 30 seconds at 30°C. The polyethyleneimine aqueous solution contained 0.03 wt% aminosilane-modified lithium-ion sieve A. Excess solution was removed from the material after wetting with the polyethyleneimine aqueous solution using a rubber roller. The volume of the polyethyleneimine dispersion was such that, relative to 1 m³, the concentration of the polyethyleneimine was... 2 The amount of aminosilane-modified lithium-ion sieve used as the substrate is 25 mg.

[0115] Then, the material was contacted with an Isopar E solution containing 0.1 wt% trimesoyl chloride (the volume of which was the same as the volume of the dispersion containing polyethyleneimine) at 30°C for 30 seconds; then the material was placed in a vacuum oven at 70°C for 5 minutes to obtain membrane M1.

[0116] Based on the reaction mechanism, it can be determined that in this embodiment, in the structural unit (I) shown in the separation layer, R1 is propyl and R2 is -O-lithium ion sieve group.

[0117] After soaking the obtained composite membrane M1 in water for 24 hours, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0118] Example 2

[0119] Similar to Example 1, except that the polyethyleneimine dispersion contains 0.08 wt% of the above-mentioned modified lithium-ion sieve. Membrane M2 was prepared.

[0120] Example 3

[0121] Same as Example 1, except that the concentration of the modified lithium-ion sieve in the polyethyleneimine dispersion is 0.2 wt%. Membrane M3 was prepared.

[0122] Example 4

[0123] Similar to Example 1, except that the modified lithium-ion sieve B from Preparation Example 2 was used. Membrane M4 was prepared. Based on the reaction mechanism, it can be determined that in this example, in the structural unit (I) of the polyamide material, R1 is propyl and R2 is an -O-lithium-ion sieve group.

[0124] Example 5

[0125] Similar to Example 1, except that the modified lithium-ion sieve C from Preparation Example 3 was used. Membrane M5 was prepared. Based on the reaction mechanism, it can be determined that in this example, in the structural unit (I) shown in the separation layer, R1 is an ethyl-n-propylamino group, and R2 is an -O-lithium-ion sieve group.

[0126] Example 6

[0127] Similar to Example 1, except that the modified lithium-ion sieve D from Preparation Example 4 was used. Membrane M6 was prepared. Based on the reaction mechanism, it can be determined that in this example, in the structural unit (I) shown in the separation layer, R1 is propyl and R2 is an -O-lithium-ion sieve group.

[0128] Example 7

[0129] Similar to Example 1, except that the modified lithium-ion sieve E from Preparation Example 5 was used. A membrane M was prepared. Based on the reaction mechanism, it can be determined that in this example, in the structural unit (I) shown in the separation layer, R1 is propyl and R2 is an -O-lithium-ion sieve group.

[0130] Example 8

[0131] Use a material with porous support and bottom layer (area 400cm²) 2The material was contacted with a 1.5 wt% piperazine dispersion at 32°C for approximately 45 seconds. The piperazine dispersion contained 0.03 wt% aminosilane-modified lithium-ion sieve A. Excess solution was removed from the material after impregnation with the polyethyleneimine dispersion using a rubber roller. The volumetric amount of the polyethyleneimine dispersion was such that, relative to 1 m³, [the solution was used to achieve the desired effect]. 2 The amount of aminosilane-modified lithium-ion sieve used as the substrate is 25 mg.

[0132] Then, the material was contacted at 32°C with an Isopar E solution containing 0.15 wt% terephthaloyl chloride (the same volume as the dispersion containing piperazine) for 45 seconds; then the material was placed in a vacuum oven at 80°C for 4 minutes to obtain membrane M8.

[0133] Example 9

[0134] Use a material with porous support and bottom layer (area 400cm²) 2 The material was contacted with a 1.2 wt% piperazine dispersion at 28°C for approximately 60 seconds. The piperazine dispersion contained 0.03 wt% aminosilane-modified lithium-ion sieve A. After impregnation with the polyethyleneimine aqueous solution, excess solution was removed using a rubber roller. The volumetric amount of the polyethyleneimine dispersion was such that, relative to 1 m³, [the solution was used to achieve the desired effect]. 2 The amount of aminosilane-modified lithium-ion sieve used as the substrate is 25 mg.

[0135] Then, the material was contacted at 28°C with an Isopar E solution containing 0.4 wt% terephthaloyl chloride (the same volume as the dispersion containing piperazine) for 60 seconds; then the material was placed in a vacuum oven at 90°C for 3.5 minutes to obtain membrane M9.

[0136] Comparative Example 1

[0137] The membrane was prepared according to the method in Example 1, except that the polyethyleneimine dispersion did not contain the aminosilane-modified lithium-ion sieve A. Membrane N1 was obtained. After soaking the obtained composite membrane N1 in water for 24 hours, the water flux and the desalination rates for magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0138] Comparative Example 2

[0139] The membrane was prepared according to the method of Example 1, except that the aminosilane-modified lithium-ion sieve A at a concentration of 0.03 wt% in the polyethyleneimine dispersion was replaced with a lithium-ion sieve Li at a concentration of 0.03 wt%. 1.33 Mn 1.67 O4 (20nm). A membrane of N2 was obtained.

[0140] After soaking the obtained membrane N2 in water for 24 hours, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured. The results are shown in Table 1.

[0141] The volumes of the polyamine dispersions in Examples 2-7 and Comparative Examples 1-2 were the same as those in Example 1; the volumes of the solutions containing polyacrylamide chlorides in Examples 2-7 and Comparative Examples 1-2 were the same as those in Example 1.

[0142] Table 1

[0143]

[0144] In Table 1, the content of modified lithium-ion sieve in the separation layer is, that is, the mass content of lithium-ion sieve relative to the total mass of polyamide material.

[0145] The thickness of the porous support layer, the thickness of the separation layer, the average pore size of the porous support layer, and the average pore size of the separation layer of the membranes obtained in the above embodiments and preparation examples are shown in Table 2.

[0146] Table 2

[0147]

[0148] The membranes in Examples 1-9 contain modified lithium-ion sieves in their separation layers. Compared to the membrane in Comparative Example 1, they have higher magnesium chloride desalination rate and water flux, higher lithium chloride permeability, and higher magnesium-lithium selectivity coefficients.

[0149] Compared to the membrane prepared by directly adding lithium-ion sieves to the aqueous phase in Comparative Example 2, the membranes in Examples 1-9 have thinner and defect-free separation layers (as evidenced by the higher MgCl2 desalination rate), higher water flux, and higher magnesium chloride rejection rate. They also exhibit good long-term cycling stability (after one week of operation, no significant changes were observed in the above parameters, while the MgCl2 desalination rate of the membrane in Comparative Example 2 decreased by approximately 2% after one week of operation). The membranes prepared in Examples 1-9, characterized by XPS (X-ray photoelectron spectroscopy), showed that after one week of operation, the loading of modified lithium-ion sieves changed within ±0.2 wt%, indicating minimal detachment. This demonstrates that the lithium-ion sieves in the separation layer of the membranes provided by this invention have strong stability and are more suitable for practical use. In contrast, the membrane prepared in Comparative Example 2, after one week of operation, showed a lithium-ion sieve loading change within the range of 3.8-7.2 wt%. This indicates that the amino-modified lithium-ion sieves, introduced onto the membrane through bonding, have a good synergistic effect with the separation layer.

[0150] Furthermore, the amino-modified lithium-ion sieve increases the compatibility with the aqueous phase and reduces the diffusion rate of monomers from the aqueous phase to the organic phase. The resulting membrane has a thinner separation layer and a suitable crosslinking density, thus exhibiting a high rejection rate even with a large water flux. Examples 1, 4, and 5 show that using an aminosilane with less steric hindrance increases the separation layer thickness under the same operating conditions, reduces the water flux of the membrane, and decreases the permeability of lithium chloride. Therefore, the membrane prepared using the method of this invention has a high water flux and a suitable pore size, exhibiting high rejection of magnesium chloride and high permeability to lithium chloride.

[0151] According to the reaction mechanism, when aminosilane and aminosilane are mixed and reacted under acidic conditions, the alkoxy group on the aminosilane can be hydrolyzed to form a Si-OH structure, which will then react with the modified lithium ion sieve to form the Si-O-lithium ion sieve structure in formula (II). Therefore, when aminosilane and aminosilane are mixed and reacted under acidic conditions, a structure with formula (II) will be obtained.

[0152] Regarding the membranes prepared in Examples 1-9: During interfacial polymerization, when the polyamine attached to the material containing the porous support and bottom layer comes into contact with the carbonyl groups of the polyacrylamide chloride, a reaction occurs to generate a polyamide framework. On the other hand, the amino-modified ion sieve in the polyamine solution undergoes an amidation reaction with other carbonyl groups in the polyacrylamide chloride that have not reacted with the polyamine to form amide bonds, together forming the separation layer structural unit shown in Formula (I). That is, other carbonyl groups in the polyacrylamide structural unit from the polyacrylamide chloride and the amino-modified lithium ion sieve form the structure shown in Formula (I). In this way, the lithium ion sieve is chemically bonded to the polyamide material and the separation layer to generate a self-polymerizing microporous thin-layer composite nanofiltration membrane. Thanks to the lithium ion sieve in the separation layer and the pore structure that matches lithium ions, the prepared membrane has good lithium ion permeability. In addition, the modified lithium ion sieve added to the aqueous phase should also inhibit the diffusion rate of the polyamine during interfacial polymerization, so that the self-limitation of the interfacial polymerization reaction occurs earlier, resulting in an ultra-thin separation layer, which greatly increases the permeability.

[0153] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing a nanofiltration separation membrane, characterized in that, The method includes: A separation layer is formed by interfacial polymerization using a dispersion containing polyamines and a solution containing polyacryl chlorides. The dispersion containing polyamines also contains an aminosilane-modified lithium-ion sieve. The aminosilane-modified lithium-ion sieve has a structure as shown in formula (II). (II) In formula (II), R1 is selected from one of C1-C6 alkylene groups, -CH2CH2NHCH2CH2CH2-, and -CH2CH2NHCH2CH2-; R2 is selected from one of H, -O-M3 group, and C1-C6 alkyl group; M1, M2, and M3 are each independently lithium ion sieves. The preparation method of the aminosilane-modified lithium-ion sieve includes: mixing the lithium-ion sieve and aminosilane in water and carrying out the modification reaction under acidic conditions; The interfacial polymerization is carried out on a substrate comprising a porous support layer and a bottom layer; the dispersion containing polyamine has a mass concentration of 0.1-3 wt%; the mass concentration ratio of aminosilane-modified lithium-ion sieve to polyamine in the dispersion containing polyamine is 1:(15-60). The polyamine is polyethyleneimine and / or piperazine; The method also includes the step of preparing a porous support layer on the substrate, the step comprising: coating a solution containing a porous support layer material onto the substrate and immersing it in water at 10-30°C for 10-60 min to form a porous support layer on the surface of the substrate; The porous support layer is made of polysulfone, and the weight-average molecular weight of the porous support layer is 50-150 kDa. When the polyamine is a polymer, the weight-average molecular weight of the polymer is 50,000-120,000 g / mol; The conditions for interfacial polymerization also include making the thickness of the separation layer 80-100 nm.

2. The method according to claim 1, wherein, The material of the bottom layer is selected from polyester and / or polyethylene; And / or, the porosity of the underlying layer is 35-60%.

3. The method according to claim 1, wherein, The conditions for preparing the porous support layer include making the thickness of the porous support layer 10-100 μm; And / or, in the solution containing the porous support layer material, the mass concentration of the porous support layer material is 10-20 wt%; And / or, the solvent in the solution containing the porous support layer material is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; And / or, the thickness of the underlying layer is 30-150 μm.

4. The method according to claim 3, wherein, The conditions for preparing the porous support layer include making the thickness of the porous support layer 30-60 μm; And / or, the thickness of the underlying layer is 50-120 μm.

5. The method according to claim 1, wherein, The interfacial polymerization method includes: sequentially contacting the surface of the substrate with a dispersion containing polyamines and a solution containing polyacrylamide chlorides.

6. The method according to claim 1, wherein, The polyacryl chloride is selected from at least one of pyromellitic chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.

7. The method according to claim 6, wherein, The polyacryl chloride is pyromellitic trimethylolpropionate chloride and / or terephthaloyl chloride.

8. The method according to claim 1, wherein, In the dispersion containing polyamine, the mass concentration of polyamine is 0.5-2.5 wt%.

9. The method according to claim 1, wherein, The mass ratio of lithium-ion sieve to aminosilane is 1:(0.1-1.5). And / or, the mass concentration of lithium ion sieves in the solution is 0.5-1.5 mg / ml; And / or, the acidic conditions are a pH of 1-3; And / or, the conditions for the modification reaction further include: a temperature of 70-90°C and a time of 5-8 hours; And / or, the preparation method of the aminosilane-modified lithium-ion sieve further includes: centrifuging, first drying, ball milling and second drying of the material obtained from the modification reaction in sequence.

10. The method according to claim 1, wherein, The lithium ion screen is selected from at least one of aluminum-based hydrotalcite bimetallic oxide lithium ion screen, manganese oxide lithium ion screen, and titanium oxide lithium ion screen. And / or, in the modification reaction, the average particle size of the lithium ion sieve is 10-200 nm; And / or, in the modification reaction, the aminosilane is selected from any one of the structures shown in formula (a)-(f); (a) (b) (c) (d) (e) (f); And / or, relative to 1m 2 The amount of aminosilane-modified lithium ion sieve used as the substrate is 5-500 mg.

11. The method according to claim 10, wherein, The lithium ions are selected from Li 1.33 Mn 1.67 O4, Li2TiO3 and Li4Mn5O 12 At least one of them.

12. The method according to claim 1, wherein, The concentration of the polyacryl chloride in the solution containing polyacryl chloride is 0.01-1 wt%.

13. The method according to claim 12, wherein, The concentration of the polyacryl chloride in the solution containing polyacryl chloride is 0.05-0.5 wt%.

14. The method according to claim 1, wherein, The contact time between the substrate and the dispersion containing polyamine is 5-100s, and the contact temperature is 20-40℃. And / or, the contact time between the substrate and the solution containing polyacrylamide chloride is 10-200s, and the contact temperature is 20-40℃; And / or, after contact with a dispersion containing a polyamine and a solution containing a polyacryl chloride, the method further includes: heat-treating the product after interfacial polymerization.

15. The method according to claim 14, wherein, The contact time between the substrate and the dispersion containing polyamine is 10-60 seconds, and the contact temperature is 28-32℃. And / or, the contact time between the substrate and the solution containing polyacrylamide chloride is 20-120 s, and the contact temperature is 28-32℃; And / or, the conditions for the heat treatment include: a temperature of 40-150°C; and a heat treatment time of 0.5-10 minutes.

16. The method according to claim 15, wherein, The heat treatment conditions include: a temperature of 50-120℃ and a heat treatment time of 1-5 minutes.

Citation Information

Patent Citations

  • Lithium-ion permselective membrane and preparation method thereof

    CN105903361A